Predictors of Surgical Outcome of Abdominal Trauma in Tertiary Care Centres of Nepal - Thapa, Bikash Bikram; Gurung, Rajan; Basnet, Robin; Thapa, Narayan (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: The abdominal trauma is a surgical emergency most of which are preventable and many of them could have good outcome with timely management by dedicated trauma system. It is not only the rising health problem but also the social and economic burden. A study on abdominal trauma can guide to cost-effective quality management of the patients. This study is undertaken to study and evaluate the predictors of surgical outcome in abdominal trauma patients in tertiary care centers in Nepal. Methods: Seventy five patients with abdominal trauma who underwent surgical intervention were evaluated prospectively inside the inclusion criteria. Ethical approval was obtained. The data on demographic pattern, clinic-radiological findings, abdominal trauma index, injury severity scale, operative findings, infectious complications, and mortality were collected. Chi square test was used for statistical analysis. Results: Out of 75 patients male to female ratio was 4.6 : 1. Blunt trauma (49) was the common cause of abdominal injury. Accidental abdominal injury happened in 73% (55) and fall from height was common mode of abdominal organ injury 40% (30). The overall morbidity and mortality were 30.6% and 9.3% respectively. Age > 30 years, Shock at presentation, Operative Delay > 24 hours, and trauma score (ATI>15 and ISS>15) were all good predictors of surgical outcome of patients with abdominal trauma (p <0.05). Conclusion: The predictors of surgical outcome were patient’s age, clinical status at presentation and delay in surgical intervention. Trauma score (both ATI and ISS) are equally important in predicting outcome which are necessary for monitoring patients care and the quality of trauma systems.